Severe Bradycardia Increases the Incidence and Severity of Torsade de Pointes Arrhythmias by Augmenting Preexistent Spatial Dispersion of Repolarization in the CAVB Dog Model - van Weperen, Valerie Y. H.; Dunnink, Albert; Bossu, Alexandre; Beekman, Jet D. M.; Meijborg, Veronique M. F.; de Bakker, Jacques M. T.; Coronel, Ruben; Varkevisser, Rosanne; van der Heyden, Marcel A. G.; Vos, Marc A. (Frontiers in Physiology, 2021)
Introduction: Torsade de Pointes arrhythmias (TdP) in the chronic AV-block (CAVB) dog model result from pro-arrhythmic factors, which trigger TdP and/or reinforce the arrhythmic substrate. This study investigated electrophysiological and arrhythmogenic consequences of severe bradycardia for TdP. Methods: Dofetilide (25µg/kg/5min) was administered to 8 anesthetized, idioventricular rhythm (IVR) remodeled CAVB dogs in two serial experiments: once under 60 beats per minute (bpm), right ventricular apex paced (RVA60) conditions, once under more bradycardic IVR conditions. Recordings included surface electrocardiogram and short-term variability of repolarization (STV) from endocardial unipolar electrograms. TdP-inducibility (≥3 episodes within ten minutes after start of dofetilide) and arrhythmic activity scores (AS) were established. Mapping experiments in ten additional dogs determined the effect of lowering rate on STV and spatial dispersion of repolarization (SDR) in baseline. Results: IVR-tested animals had longer baseline RR (1403±271ms) and repolarization intervals than RVA60-animals. Dofetilide increased STV similarly under both rhythm strategies. Nevertheless, TdP-inducibility and AS were higher under IVR-conditions (6/8 and 37±27 vs 1/8 and 8±12 in RVA60, respectively, both p<0.05). Mapping: Pacing from high (128±10bpm) to middle (88±10bpm) to experimental rate (61±3bpm) increased all electrophysiological parameters, including interventricular dispersion, due to steeper left ventricular restitution curves, and intraventricular SDR: maximal cubic dispersion from 60±14 (high) to 69±17 (middle) to 84±22ms (p<0.05 vs high and middle rate). Conclusion: In CAVB dogs, severe bradycardia increases the probability and severity of arrhythmic events by heterogeneously causing electrophysiological instability, which is mainly reflected in an increased spatial, and to a lesser extent temporal, dispersion of repolarization.